Pengaruh Digitalisasi terhadap Perkembangan Industri Halal di Indonesia - Cory Vidiati; Nur Wulan Ramdhaniah (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
Advances in digital technology have brought about significant changes in various economic sectors, including the halal industry. Digitalization plays a crucial role in increasing competitiveness, efficiency, and expanding the market for halal businesses in Indonesia. This study aims to analyze the impact of digitalization on the growth of the halal industry in Indonesia and identify the opportunities and challenges faced during the digital transformation process. The strategy employed in this study is a qualitative approach through library research. Information was obtained from various secondary sources, such as academic articles, books, scientific journals, and reports from relevant institutions discussing digitalization and the halal industry. Data analysis was conducted using a descriptive qualitative approach through the review and interpretation of various pieces of information related to the research issue. The research findings indicate that digitalization has a positive effect on the growth of the halal industry by opening market access, improving operational efficiency, strengthening information transparency, and increasing consumer trust in halal products. Digital technology also assists in the halal certification process and the development of halal MSMEs to be more competitive in the digital economy. However, the implementation of digitalization still faces several challenges, such as low digital literacy, a lack of technological infrastructure, and the need for skilled human resources. Therefore, synergy between the government, business actors, and various stakeholders is very important to optimize the use of digital technology in supporting the development of the halal industry in Indonesia.